2001
DOI: 10.1016/s0378-1097(01)00059-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacterial RNA polymerase by the cyanobacterial metabolites 12-epi-hapalindole E isonitrile and calothrixin A

Abstract: The alkaloid 12-epi-hapalindole E isonitrile, from a cyanobacterial Fischerella species, and the indolophenanthridine calothrixin A, from Calothrix, inhibited Escherichia coli RNA polymerase competitively with respect to ATP, and non-competitively with respect to UTP. The inhibition was dependent on the order of addition of the inhibitors. The K I values, with ATP as the variable substrate, were 1.3 þ 0.2 mM and 0.23 þ 0.11 mM, respectively. Based on comparisons with the sensitivity of whole cells to these inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…Several recent reviews have discussed their potential as a source of pharmaceutical leads (Sielaff et al , 2006; Tan, 2007; Williams, 2009). One family of compounds that has been explored for their pharmaceutical potential are isonitrile containing indole alkaloids, such as hapalindoles (Doan et al , 2001; Huber et al , 1998; Klein et al , 1995; Moore et al , 1987; Moore et al , 1989), ambiguine isonitriles (Huber et al , 1998; Raveh and Carmeli, 2007; Smitka et al , 1992), fischerindoles (Park et al , 1992) and wetwitindolinones (Jimenez et al , 1999; Stratmann et al , 1994) from branched filamentous cyanobacteria of the genera Fischerella , Hapalosiphon , Westiella , and Westiellopsis . Since the first report of hapalindoles in 1984 by Moore and coworkers (Moore et al , 1984), over 60 natural products belonging to this family have been identified (Richter et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reviews have discussed their potential as a source of pharmaceutical leads (Sielaff et al , 2006; Tan, 2007; Williams, 2009). One family of compounds that has been explored for their pharmaceutical potential are isonitrile containing indole alkaloids, such as hapalindoles (Doan et al , 2001; Huber et al , 1998; Klein et al , 1995; Moore et al , 1987; Moore et al , 1989), ambiguine isonitriles (Huber et al , 1998; Raveh and Carmeli, 2007; Smitka et al , 1992), fischerindoles (Park et al , 1992) and wetwitindolinones (Jimenez et al , 1999; Stratmann et al , 1994) from branched filamentous cyanobacteria of the genera Fischerella , Hapalosiphon , Westiella , and Westiellopsis . Since the first report of hapalindoles in 1984 by Moore and coworkers (Moore et al , 1984), over 60 natural products belonging to this family have been identified (Richter et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial activity of algal alkaloids may be attributed to their ability for inhibition of RNA polymerase of E. coli result in inhibited both RNA and protein synthesis ( Doan et al, 2001), alkaloid also inhibit DNA synthesis by inhibition of the topoisomerase enzyme that control the DNA replication of E. coli leading to morphological changes and cell lysis ( Karou et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Calothrixin A is known to be a N ‐oxide analog of calothrixin B. Calothrixins exhibit excellent antimalarial activity including inhibitory effects on a chloroquine resistant strain of the malarial parasite Plasmodium falciparum . They show antiproliferative properties against several cancer cell lines as well as human DNA topoisomerase I poisoning activity [2] and also act as inhibitors of bacterial‐RNA polymerase [3] . In addition, calothrixin A is also known to induce the intracellular formation of reactive oxygen species [4] .…”
Section: Figurementioning
confidence: 99%